1992
DOI: 10.4327/jsnfs.45.271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Globin Powder on Bone Mineral Density in Model Rats with Postmenopausal Osteoporosis.

Abstract: Insufficient intake of calcium is one of the risk factors for osteoporosis.Recently, many studies have investigated calcium sources and various food components influencing calcium metabolism. In this study, the bone mineral density (BMD) of the lumbar spine and tibia was measured by dual energy X-ray absorptiometry (DEXA) in order to examine the effect of globin powder, a polypeptide mixture (average M.W., 8000), on bone metabolism in model rats with postmenopausal osteoporosis. Six-week-old SD-strain female r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Deve-se levar em consideração, no momento do planejamento dietético, não somente a proporção Ca/P da dieta, como também a origem (animal ou vegetal) do P dietético para prevenção/tratamento da osteoporose (36) .…”
Section: Papel Dos Minerais Na Saúde óSseaunclassified
“…Deve-se levar em consideração, no momento do planejamento dietético, não somente a proporção Ca/P da dieta, como também a origem (animal ou vegetal) do P dietético para prevenção/tratamento da osteoporose (36) .…”
Section: Papel Dos Minerais Na Saúde óSseaunclassified
“…We have reported that the globin preparation might elevate intestinal Ca absorption (10). On the other hand, in the bone from vitamin D-deficient rats, either there is no osteoinductive activity or there is a smaller amount of osteoinduc tive activity.…”
Section: Discussionmentioning
confidence: 96%
“…We have reported that a dietary globin preparation is effective for increasing bone mineral density (BMD) and physical bone strength in experimental animals (10). The globin powder is thought to be effective in increasing intestinal Ca absorption (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The muscles and connective tissues were carefully removed. Thereafter the bone mineral density (BMD) of the fourth and fifth lumbar vertebrae (L4, L5) were measured by dual energy X-ray absorptiometry [DEXA (Hologic's QDR-1000 X-ray bone densitometer)] as previously reported (7). Moreover, whole tibias were measured by DEXA.…”
mentioning
confidence: 99%